MICROGEN IMPLEMENTATION FOR BUILDING ONLINE LEARNING MANAGEMENT SYSTEM WITH MICROSERVICES AND GRAPHQL GENERATOR APPROACH - Tinambunan, Daniel Hasiholan; Ahmad Baehaqi; Refgiufi Patria Avrianto; Richardus Eko Indrajit (Informatika, Universitas Jenderal Soedirman, 2023)
In an era of education marked by digital transformation, developing a Learning Management System (LMS) can be a challenge that requires an innovative approach. This study proposes a solution by combining the Microgen concept, Microservices approach and GraphQL generator in the development of a revolutionary LMS Pradita. Thanks to this advanced integration, this research succeeded in designing a database schema with MgSchema visualization, enabling adaptive data manipulation with Microgen functions and simplifying development, developing a responsive interface through the GraphQL generator. Thus, this research not only discusses the intricacies of LMS development, but also provides valuable guidance for developers to face the challenges of modern and cutting-edge education.